Constructivism-Based Learning Module for Middle School Students' Creative Thinking on the Interaction of Living Things and Their Environments - Rosalina, Yarlis; Yustina, Yustina; Suzanti, Fitra (Journal of Educational Sciences, 2021)
Constructivism-based learning module research aims to analyze the effect of using the module on the creative thinking of junior high school students regarding the interaction of living things and their environment. This quasi-experimental study used the Pretest Posttest Control Group design with the research subjects being grade VII students of SMP Negeri 2 Kampar. At the beginning of the implementation, students were given creative thinking pretest questions, then students studied constructivism-based learning modules and were given posttest questions. The parameters of creative thinking are 4 indicators, each indicator has 5 questions. Hypothesis analysis using t-test. The results showed that the control class has an average pretest of 61.75 (quite creative). Meanwhile, in the experimental classhas an average posttest of 81.25 (creative). The results of hypothesis testing show tcount > ttable with a value of 3.891 > 2.010. In conclusion, the use of constructivism-based learning modules has an effect on increasing students' creative thinking regarding the interaction of living things and their environment.